Perancangan Antena Mikrostrip Patch Square Pada Frekuensi 2.4 GHz - Amar Ma'ruf (Jurnal Teknologi Terpadu, 2018)
A microstrip antenna is an antenna consisting of very thin radiation elements (conductors) placed in a ground plane, where the patch and ground plane are separated by a substrate. Microstrip antennas have many beneficial properties such as low cost, ease of modeling and fabrication and are able to provide better performance. This is very suitable for data communication devices via wireless LAN that continue to increase. Wireless LAN technology recommended by IEEE 802.11. in this study the antenna that will be designed is a microstrip patch square antenna with E-Shaped technique. The type of substrate used is FR4-Epoxy. The application used to design microstrip antennas is Ansoft HFSS 13.0. The antenna is designed to work at a 2.4 GHz frequency, with a patch dimension of 29 mm. from the simulation results obtained a gain value of 5.53 dB. While the VSWR value is obtained at 1.2. Return loss value is obtained at -20.80 dB. In the field measurement results, WirelessMon software is used, where the signal amplification without using an antenna at a distance of> 50 m of the amplified signal is not detected, while using the antenna signal gain is -83 dBm.